IMPLEMENTASI METODOLOGI DAKWAH MELALUI LEMBAGA MASJID JAMI’ AR-ROHMAT PLUMPANG DALAM MENINGKATKAN ANTUSIAS MASYARAKAT - Siti Kris Fitriana Wahyu Lestari; Mohammad Abdul Jabbar (ASWALALITA: Journal of Da'wah Management, 2023)
Dakwah is a series of ways to call upon Islamic teachings to do good deeds, prevent evil in a wise way without coercion in order to get happiness in this world and in the hereafter. Dakwah is not limited by space and time. In preaching there are several points that need to be carried out by preachers including, preaching really needs an appropriate methodology of preaching, in order to create effective and efficient preaching. Such as the methodology contained in the great mosque institution Ar-Rohmat Plumpang Tuban.To facilitate this research, the researcher used a descriptive qualitative research method. This research was conducted at the Ar-Rohmat Plumpang Tuban grand mosque. Observations and in-depth interviews were conducted to collect data. Other data sources are obtained from books, journals, and all research supporting data. This research resulted in several findings including: it is known that the da'wah methodology found in the great mosque of Ar-Rohmat Plumpang Tuban uses the da'wah bil wisdom (preaching wisely) method, and mau'idza hasanah (advising), mujadallah al-hasan (debate), and bil things (circumstances). Second, in conveying the message of his da'wah it is very interesting and makes the community enthusiastic in following it. In addition, this research will investigate how preaching also requires efforts to deal with challenges and obstacles so that the goals of da'wah can be achieved and can be said to be effective and efficient.